Exploring STEM education through pre-service teacher conceptualisations of mathematics - Cooke, Audrey; Walker, R. (2015)
STEM education is advocated as enhancing learning in the areas of Science, Technology, Engineering and Mathematics through delivering meaningful learning experiences to students. Although the benefits of integrating STEM into school curricula appear to warrant implementation, observations are that many teachers and pre-service teachers are not adopting STEM education. Opportunities to address STEM education with pre-service teachers may be stymied by the pre-service teachers' conceptualisations of how they use mathematics and how their students will use the mathematical concepts learnt in the classroom. This study examined links between pre-service teachers' perceptions of their use of mathematics in their everyday lives and their beliefs regarding the relevance of classroom mathematics to students' everyday lives. The participants (n=698) were first year Early Childhood and Primary pre-service teacher education students and they completed an instrument measuring their conceptualisations of mathematics. Pre-service teacher profiles were created based on the level of agreement indicated towards specific statements based on how mathematics was conceptualised from the data collected. Results suggest that pre-service teachers' conceptualisations of mathematics relates to their attitudes towards their use of mathematics in their everyday lives, numeracy in everyday life, and classroom mathematics. The study proposes that pre-service teachers' personal use of mathematics in decision making and the perception of the relevance of mathematics to children's everyday lives are identification factors in STEM being integrated into their teaching practice. Discussion of this research centres on the potential implications for the development of STEM experiences in pre-service teacher education.